Antworten:
# x ^ 2 + x-1 = 0, x! = 0 #
Erläuterung:
# x / x-2 + x-1 / x + 1 = -1 #
mal # x #:
#x (x / x-2 + x-1 / x + 1) = x (-1) #
# x-2x + x ^ 2-1 + x = -x #
# x-2x + x ^ 2-1 + x + x = 0 #
# x ^ 2 + x-1 = 0 #
Antworten:
Wenn du meinst # x / (x-2) + (x-1) / (x + 1) = - 1 # dann bekommen wir
# x = 0 #
oder # x = 1 #
Erläuterung:
Es muss sein
#xne 2 # und #xne -1 #
Multiplizieren mit
# (x + 1) (x-2) #
wir erhalten
#x (x + 1) + (x-1) (x-2) = - (x + 1) (x-2) #
multiplizieren aus
# x ^ 2 + x + x ^ 2-x-2x + 2 = -x ^ 2-x + 2x + 2 #
Sammeln
# 3x ^ 2-3x = 0 #
oder
# 3x (x-1) = 0 #
so
# x = 0 #
oder
# x = 1 #